Changes in Subsidized Fertilizer Policy on Factors of Production and Farm Income of Red Chili (Capsicum Annuum L) in Cianjur Regency - Dety Sukmawati; Euis Dasipah; Asiah Nurdin (Greenation Research & Yayasan Global Resarch National, 2023)
Changes in subsidized fertilizer policies are felt to have a direct effect on the use of production factors and the income of red chili farmers. Data from the Central Statistics Agency for 2022 shows a decrease in the harvested area of ??1,380 Ha (58%) and production of 13,830.8 tons (53%) of red chilies in Cianjur Regency. This is the basis for research whether the decline in production is one of the impacts of changes in subsidized fertilizers. The research method is descriptive verification, the analysis technique used is multiple linear regression. The number of samples taken is 75 red chili farmers in Cipanas District. Subsidized fertilizer policy is one of the government policies in an effort to improve the economy of the farming community. However, these policy changes can have a significant impact on production factors and farmer incomes. This study reveals that changes in subsidized fertilizer policies have a significant effect on the income of red chili farmers. Changes in the policy of reducing the type of fertilizer and the allocation of fertilizer subsidies by 10% reduced farmers' income by 4.68%. Factors of Production affect the Income of Red Chili Farmers where changes in the use of factors of production after Minister of Agriculture No. 10 of 2022 where the type of fertilizer and the dosage of subsidized fertilizers change results in reduced farmer income. This study concludes that the income of red chili farmers is significantly influenced by production factors. After the enactment of the Minister of Agriculture, every change in the use of production factors by 10% in Production Factors contributed to an increase in farmers' income by 3.16%.